2007
DOI: 10.1002/nau.20459
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for neuromodulation of the lower urinary tract

Abstract: Patients with symptoms of overactive bladder syndrome or non-obstructive urinary retention, refractory to conservative therapy, can nowadays be treated minimally invasively with sacral nerve stimulation (SNS). The use of electric currents to treat urological pathology has a long history but SNS therapy only received FDA approval in 1997. The mechanisms of action are still not known so there are different theories explaining the modulation effect. Recent studies have shown a central modulation effect. Predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Sacral neuromodulation (SNM) has emerged as a successful treatment for urinary voiding disorders and lower bowel motility disorders in recent years [1, 2]. However, understanding and knowledge about the underlying mechanism of action for urological disorders as well as lower bowel motility disorders remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Sacral neuromodulation (SNM) has emerged as a successful treatment for urinary voiding disorders and lower bowel motility disorders in recent years [1, 2]. However, understanding and knowledge about the underlying mechanism of action for urological disorders as well as lower bowel motility disorders remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation can be practiced in any of the sacral nerves, but the lower ones are more preferred, as the incidence of the nerve root and vascular structures greatly increases in the higher sacral nerves when compared to the lower ones [ 17 ]. A procedure at the level of S3 produces the best motor response [ 18 ]. In a study conducted by Hasan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients have undergone both behavioral therapy and medication therapy. However, approximately 40% of patients either do not achieve the expected therapeutic effects or are utterly intolerant to the treatment ( 12 ). It has been demonstrated that OAB significantly reduces quality of life and can lead to sleep disturbances and a decline in sexual function ( 2 ).…”
Section: Discussionmentioning
confidence: 99%